A compendium of sugar amino acids (SAA): scaffolds, peptide- and glyco-mimetics - Risseeuw, M; Overhand, M; Fleet, G; Simone, M (2007)
Sugar amino acids (SAAs) are carbohydrate derivatives bearing both amino and carboxylic acid functionalities. SAAs are very versatile conformationally biased building blocks amenable to serve as glyco- or peptidomimetics. The stereochemical arrangement of the substituents of the sugar ring, its ring-size as well as the presence of additional functional groups provides a plethora of possible combinations. In this overview the structures of oxygen heterocylic SAAs that have been reported thus far are provided, having 3, 4, 5, 6-membered rings as well as several bicyclic counterparts. © 2007 Elsevier Ltd. All rights reserved.